2011
DOI: 10.1002/jcb.23129
|View full text |Cite
|
Sign up to set email alerts
|

Loop domain organization of the p53 locus in normal and breast cancer cells correlates with the transcriptional status of the TP53 and the neighboring genes

Abstract: P53 is a tumor suppressor protein critical for genome integrity. Although its control at the protein level is well known, the transcriptional regulation of the TP53 gene is still unclear. We have analyzed the organization of the TP53 gene domain using DNA arrays in several breast cancer and control cell lines. We have found that in the control breast epithelial cell line, HB2, the TP53 gene is positioned within a relatively small DNA domain, encompassing 50 kb, delimited by two nuclear matrix attachment sites.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…[33] found that in natural aging of the rat liver, the average DNA loop size gradually decreases, and DNA loops increase in number with the gradual loss of proliferating potential and with the progression towards terminal differentiation. More recently, it has been shown that in breast cancer cell lines the dimension of chromatin loops are larger as compared to that of normal cells [34]. These results are in agreement with the data reported above.…”
Section: Discussionsupporting
confidence: 91%
“…[33] found that in natural aging of the rat liver, the average DNA loop size gradually decreases, and DNA loops increase in number with the gradual loss of proliferating potential and with the progression towards terminal differentiation. More recently, it has been shown that in breast cancer cell lines the dimension of chromatin loops are larger as compared to that of normal cells [34]. These results are in agreement with the data reported above.…”
Section: Discussionsupporting
confidence: 91%
“…The tumor suppressor gene TP53 is one of the most studied genes implicated in cancer and, despite a huge knowledge on its post-translational regulation [31,32], its transcription control and genomic domain are not very well established [33]. In a previous work we described MARs in a genomic region of 167 kb containing the TP53 and neighboring genes, using different cell lines [27]. Here we concentrated our study on two MARs, namely MAR2 and MAR3.…”
Section: Results and Discussion Association Of S/mars In Breast Cellmentioning
confidence: 99%
“…1, A). This organization is perturbed in cancerous cell lines MDA-MB-231, BT-474, T47D and MCF-7 [27]. Chromatin is composed of DNA and proteins, mostly histones, which are involved in genomic DNA organization in the nuclei.…”
Section: Results and Discussion Association Of S/mars In Breast Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…HB2 cells were selected for their ability to undergo branching morphogenesis from spherical structures when cultured in collagen gels and stimulated by hepatocyte growth factor and used as a cell model system for the study of the involvement of fibroblast-derived growth factor, Wnt, and integrins in mammary tissue development (Huguet et al 1995;Alford et al 1998). Subsequently, HB2 cells have been used as non-neoplastic counterpart for elucidating various biochemical and genetical aspects of normal and tumoral breast cell biology, such as Wnt5a-and heregulinstimulated signal transduction pathways (e.g., Baeckström et al 2000a;Jönsson and Andersson 2001;Dejmek et al 2003), c-ERBb2 promotion of apoptosis and effect on MUC1 expression (e.g., Baeckström et al 2000b;Scibetta et al 2001), ethanol promotion of cell invasion (e.g., Aye et al 2004), cadmium-mediated changes in gene expression (Sirchia et al 2008;Sirchia and Luparello 2009), TP53 transcriptional regulation (Goes et al 2011), and epigenetic modulation of oncosuppressor genes (Rubinek et al 2012).…”
Section: Introductionmentioning
confidence: 99%